DOWRY PRACTICES IN LAMPUNG PESISIR TRADITIONAL MARRIAGES: AN ISLAMIC LEGAL PERSPECTIVE - Susanti, Restika (Indonesia Private Law Review, 2024)
In Indonesia, Islamic law requires that the giving of a dowry in marriage involves mutual agreement between the prospective groom and bride. In Padang Ratu Village, the practice of dowry does not deviate from Islamic principles. Instead, the dowry amount is agreed upon by both parties, influenced by the prospective bride's family's demands for specific amounts and forms of dowry, which may include money and goods. If the prospective groom’s family agrees to these terms, the marriage can proceed. This research explores two main questions: the implementation of traditional dowry practices in Lampung Pesisir, Padang Ratu Village, Wonosobo District, Tanggamus Regency, and the Islamic legal perspective on these practices. The research employs normative legal research with a descriptive approach, utilizing historical and legislative methods. Secondary data are analyzed qualitatively. The findings indicate that while only half of the dowry amount is explicitly mentioned during the marriage consent process classifying it as musamma dowry the practice of providing dowry in the form of goods does not contravene Islamic law.